2003
DOI: 10.5380/rsa.v4i1.1059
|View full text |Cite
|
Sign up to set email alerts
|

Fitoreguladores E Germinação De Sementes De Maracujá Doce Em Condições De Laboratório

Abstract: O experimento conduzido no Laboratório de Análise de Sementes do Departamento de Produção Vegetal - Setor Agricultura da Faculdade de Ciências Agronômicas do campus de Botucatu - UNESP, teve como objetivo avaliar a influência de fitorreguladores na germinação de sementes de Passiflora alata Curtis. Foram avaliados 14 tratamentos sob o delineamento experimental inteiramente casualizado com 4 repetições de 50 sementes cada. Os tratamentos constaram da aplicação dos fitorreguladores GA3, fenilmetiltetrahidro- pir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
(7 reference statements)
1
3
0
1
Order By: Relevance
“…Similar results were found by Zucareli et al (2003), who tested the application of gibberellin acid in Passiflora alata seeds, another species of the genus Passiflora, and concluded that the growth regulator did not favor the seed germination process. They concluded that the germination performance was limited due to hormonal imbalance promoted by the application of plant regulators at doses inadequate to the species.…”
Section: Resultssupporting
confidence: 81%
“…Similar results were found by Zucareli et al (2003), who tested the application of gibberellin acid in Passiflora alata seeds, another species of the genus Passiflora, and concluded that the growth regulator did not favor the seed germination process. They concluded that the germination performance was limited due to hormonal imbalance promoted by the application of plant regulators at doses inadequate to the species.…”
Section: Resultssupporting
confidence: 81%
“…Estudos têm demonstrado que as giberelinas, citocininas e o etileno são capazes de estimular a germinação de sementes de espécies de maracujazeiros, podendo ser citados como exemplos os trabalhos realizados por Coneglian et al (2000), Ferreira et al (2001), Zucareli et al (2003), Ferrari (2005) …”
Section: Introductionunclassified
“…Moreover, the lack of reference of TZ staining patterns for Passiflora makes it difficult to evaluate the results. In some studies in which the TZ test was performed to evaluate the viability of Passifloraceae seeds, such as in P. alata (Zucareli et al, 2003;Ferreira et al, 2005) and P. setacea (Pádua et al, 2011), no images were provided that could be used for comparison with other species, such as in the present study (P. foetida var. glaziovii).…”
Section: Discussionmentioning
confidence: 99%
“…glaziovii). When the hard seeds of P. alata were evaluated by the TZ test to determine the percentage of dormant and damaged seeds, viable seeds showed red or pink staining, whereas unviable seeds were milky-white or red (Zucareli et al, 2003). Pádua et al (2011) evaluated the seeds of P. setacea and observed that viable seeds showed pinkish colouration in at least half of the cotyledons and throughout the embryonic axis.…”
Section: Discussionmentioning
confidence: 99%